Knowledge of and adherence to standard precautions in a hemodialysis unit: a cross-sectional study - Medeiros, Laura Prado; Miranda, Kamila Silva de; Gonçalves, Thayna Martins; Rodrigues, Deusdélia Dias Magalhães; Hiraki, Karen Renata Nakamura; Valim, Marilia Duarte; Taminato, Monica; Morais, Richarlisson Borges de (São Paulo Medical Journal, 2022)
BACKGROUND: Standard precautions (SPs) are recommended safety measures for healthcare professionals to follow, with a view to preventing healthcare-related infections (HCRIs) and for their own protection. Inadequate adherence to these measures can lead to occurrences of occupational accidents and HCRIs. OBJECTIVES: To ascertain the knowledge of and adherence to SP measures among the nursing staff of a hemodialysis service and the relationship of these variables to occurrences of work accidents with biological material. DESIGN AND SETTING: Descriptive cross-sectional and correlational study with a quantitative approach developed in a hemodialysis clinic in Minas Gerais. METHODS: Data were collected through sociodemographic questionnaires and questionnaires on knowledge of and adherence to SPs. RESULTS: 29 professionals participated in the study. It is noteworthy that all of them had already participated in training related to SPs. However, no relationship was identified between knowledge of (15.17 points) and adherence to (71.86 points) SPs. In addition, inferential analysis showed that there was a relationship between suffering a work accident with biological material and the sociodemographic data and knowledge of and adherence to standard precautions. CONCLUSION: Knowledge of the SPs that had been established did not mean mastery of the subject. Despite positive results regarding adherence, factors requiring improvement were observed. It was possible to infer the characteristics that gave rise to greater risk of occurrences of accidents at work. Thus, this study showed the importance of assessing knowledge of and adherence to SP, in order to optimize and direct continuing education towards resolving occupational exposure.